Aspects of the Canadian evangelical experience - Rawlyk, George A. (McGill-Queen's studies in the history of religion., 1997)
Aspects of the Canadian Evangelical Experience explores Canadian evangelicalism in the nineteenth and twentieth centuries, placing it within historical, cultural, and theological frameworks. --from publisher description.